The legal relevance of unilateral copyright statements on websites - D. I. Shmatkov; D. V. Pashniev; O. V. Khliestkov; S. O. Kolomiitsev (Bulletin of Kharkiv National University of Internal Affairs)
The presented study is aimed at determining the current state of the legal context and legal consequences of the formulation of certain components of unilateral copyright statements on websites. In the research process, such methods as analysis and synthesis, induction and deduction, methods of generalization, study of documentation and methods of descriptive statistics were used.